Process design and exergy cost analysis of a chemical looping ammonia generation system using AlN/Al2O3 as a nitrogen carrier - Wang, Xiaoyu; Su, Mingze; Zhao, Haibo (Energy (Oxford), 2021)
Chemical looping ammonia generation (CLAG), in which the N2 fixation and hydrolysis reactions occur via the circulation of nitrogen carriers, has the advantages of low-pressure, low energy consumption and high ammonia yield. Therefore, CLAG is considered as a promising alternative to conventional Haber–Bosh technology. In this work, a model for the CLAG system with a capacity of 300,000 t/a is first established. For the simulation, the N2 fixation and hydrolysis reactors are modeled as the kinetics-based mixed flow reactor, and AlN/Al2O3 is used as the nitrogen carrier. The optimal operation conditions of the CLAG system are then determined by sensitivity analyses. The distribution of the exergy loss is gained from exergy analysis. The results showed that the exergy efficiency of the system reached to about 26%. Finally, exergy cost analysis is conducted to evaluate the cost formation of the system. Generally, the unit exergy cost of heat exchangers is larger than those of the other components. The distillation tower in air separation unit, the N2 fixation reactor, and the compressor in compression and purification unit should be primarily considered in system improvement because of the significant effects of their irreversibilities on other components. •A chemical looping ammonia generation (CLAG) system was developed.•Reaction kinetics was transformed and imported into the simulation model.•Both exergy and exergy cost analyses were conducted for the CLAG system.•The exergy efficiency of the proposed CLAG system reached to 26%.